CO2 and CH4 fluxes from inundated floodplain ponds: role of diel variability and duration of inundation - Rulík, Martin; Weber, Lukáš; Min, Saw; Šmíd, Radovan (Frontiers in Environmental Science, 2023)
Small waterbodies like floodplain ponds are considered to be an important component of the global carbon budget. Although they are found in huge numbers worldwide and their numbers are increasing every year due to the creation of new ponds, we do not yet have sufficient data on direct estimates of emission fluxes from these waterbodies. Here we present results from a set of 24 ponds located in the Morava river floodplain, Czech Republic. The ponds varied in their origin (man-made vs natural), size, depth, sediment organic matter content, and macrophyte growth. Water chemistry parameters, concentrations and exchange of CO2 and CH4 with the atmosphere were directly measured during the day and night from spring to summer 2020. The ponds emitted more CO2 and CH4 during a night-time, both CO2 and in particular CH4 emissions tended to increase with the duration of pond inundation. Total diffusive fluxes of CO2 and CH4 into the atmosphere ranged from -37072.9 – 432683,3 µmol m-2d-1, and -11485.28 – 95889.58 µmol m-2 d-1, respectively. Generally, all ponds were found to be a net source of CO2 and CH4 to atmosphere. In average, ponds emitted 7,64 g CO2-equivalent m-2 d-1. Thus, our results indicate that floodplain ponds are important source of both the CO2 and CH4 to the atmosphere and they should not be omitted in regional carbon budget.